Mineral bone disorder in children with chronic kidney disease: Data from the KNOW-Ped CKD (Korean cohort study for outcome in patients with pediatric chronic kidney disease) study - Jung, Jiwon; Lee, Keum Hwa; Park, Eujin; Park, Young Seo; Kang, Hee Gyung; Ahn, Yo Han; Ha, Il-Soo; Kim, Seong Heon; Cho, Heeyeon; Han, Kyoung Hee; Cho, Min Hyun; Choi, Hyun Jin; et al. (Frontiers in Pediatrics, 2023)
Background: Children with chronic kidney disease (CKD) are at high risk of mineral bone disorder (MBD), which leads to fractures, growth retardation, and cardiovascular disease. We aimed to comprehensively understand the relationship between renal function and factors related to MBD and evaluate the prevalence and distribution characteristics of MBD, specifically among Korean patients from the KNOW-PedCKD cohort. Methods: From the baseline data of the KNOW-PedCKD cohort, we examined the prevalence and distribution of MBD in 431 Korean pediatric CKD patients, including the level of corrected total calcium, serum phosphate, serum alkaline phosphatase, serum intact parathyroid hormone (iPTH), fibroblast growth factor 23 (FGF-23), serum vitamin D, fractional excretion of phosphate (FEP), and bone densitometry Z-scores. Results: The median serum calcium level remained relatively normal regardless of the CKD stage. The levels of 1,25-dihydroxy vitamin D, urine calcium-to-creatinine ratio, and bone densitometry Z-score significantly decreased with advancing CKD stage, while those of serum phosphate, FGF-23, and FEP significantly increased with CKD stage. The prevalence of hyperphosphatemia (17.4%, 23.7%, and 41.2% from CKD stages 3b, 4, and 5, respectively) and hyperparathyroidism (37.3%, 57.4%, 55.3%, and 52.9% from CKD stages 3a, 3b, 4, and 5, respectively) significantly increased with the CKD stage. Prescriptions of medications, such as calcium supplements (39.1%, 42.1%, 82.4%), phosphate binders (39.1%, 43.4%, 82.4%), and active vitamin D (21.7%, 44.7%, and 64.7%) significantly increased with CKD stage 3b, 4, and 5, respectively. Conclusions: The results demonstrated the prevalence and relationship of abnormal mineral metabolism and bone growth according to CKD stage in Korean pediatric CKD patients for the first time.